A study of optimal control approaches of water-to-water CO2 heat pump for domestic hot water use - Yantong Li; Natasa Nord; Huibin Yin; Gechuanqi Pan; Changhong Wang; Tingting Wu; Inge Håvard Rekstad (Case Studies in Thermal Engineering)
Carbon dioxide (CO2) heat pumps are not causing ozone layer depletion, while offering high temperature water. Typical control (TC) can realize normal operation of water-to-water CO2 heat pump. However, the approach for developing model-based optimal control (MC) for further improving the performance of water-to-water CO2 heat pump is still lacking. Hence, this study presents MC approaches for water-to-water CO2 heat pump. The developed model-based controller was composed of the optimization strategy and system models. The objective of optimization strategy was to maximize system coefficient of performance by identifying optimal setpoint values of discharge pressure and outlet water temperature at the gas cooler side. System models of compressor power and heat rate at the gas cooler side were established using large amount of data from virtual CO2 heat pump. The reliability of virtual CO2 heat pump was validated by experimental data. Results of case studies demonstrated that the system coefficient of performance with MC could be improved by 7.8 %–14.6 % in comparison with that with TC. This study therefore gave a guideline for optimal control of water-to-water CO2 heat pump.